Use, Yield, and Risk of Device-assisted Enteroscopy in the United States: Results From a Large Retrospective Multicenter Cohort. Issue 9 (October 2021) - Noujaim, Michael G.; Parish, Alice; Raines, Daniel; Gross, Seth A.; Cave, David; Vance, Iris; Beyer, David; Liu, Diana; Hoffman, Benjamin; Lawrence, Zoe; Castillo, Gabriel; Pavri, Tanya; et al.
Abstract : Introduction: Since 2001, device-assisted enteroscopy (DAE) has revolutionized the diagnostic and therapeutic capabilities for managing small bowel pathology. Though commonly performed, there have been no recent large studies to assess the use, yield, and risks of DAE and none that include all 3 DAE modalities. We hypothesized that DAE is safe with high diagnostic and therapeutic yields achieved within reasonable procedure duration and here we present a large retrospective multicenter US study evaluating the use, yield, and complications of DAE. Methods: After obtaining institutional review board approval, electronic records were used to identify all DAE's performed for luminal small bowel evaluation in adult patients at 4 US referral centers (Duke University Medical Center, New York University Langone Medical Center, Louisiana State University Health Sciences Center, and University of Massachusetts Medical Center) from January 1, 2014 to January 1, 2019. Electronic medical records were reviewed to collect and analyze a variety of procedure-related outcomes. Using the data pooled across centers, descriptive statistics were generated for the patient and procedure-related characteristics and outcomes; relationships between characteristics and outcomes were explored. Results: A total of 1787 DAE's were performed over this 5-year period (392 at Duke University Medical Center, 887 at Louisiana State University Health Sciences Center, 312 at New York University Langone Medical Center, and 195 at University of Massachusetts Medical Center). Of these, there were 1017 (57%) double-balloon, 391 (29%) single-balloon, and 378 (21%) spiral enteroscopies. The mean age of patients undergoing DAE was 66 years and 53% of examinations were performed on women; 18% of patients in the cohort underwent >1 DAE over this time span. A total of 53% of examinations were performed for suspected small bowel bleeding, 31% were directly guided by video capsule endoscopy findings and 8% were performed for abnormal imaging. A total of 85% of examinations used an antegrade approach and DAE took a mean of 45 minutes to complete; 76% of examinations revealed abnormal findings, with vascular, inflammatory, and neoplastic findings seen in 49%, 17%, and 15% of the cohort, respectively. Older age was significantly associated with any abnormal finding, including arteriovenous malformations ( P <0.0001); 50% of examinations included a therapeutic maneuver, most commonly argon plasma coagulation/cautery (43%). There were complications in 16 examinations (0.9%) including 2 perforations (0.1%), 6 cases with bleeding (0.3%) and 1 episode of pancreatitis (0.1%). Conclusions: DAE is most commonly performed to evaluate suspected small bowel bleeding and is commonly directed by video capsule findings. DAE is safe, has a high diagnostic yield, with 76% of examinations showing abnormal findings, and frequently features therapeutic maneuvers. Advancing age is associated with abnormal findings on DAE.